Pelatihan Pembuatan Web Untuk Penerapan Sistem Informasi Pendidikan pada Pengolahan Data Alumni: Pelatihan Pembuatan Web Untuk Penerapan Sistem Informasi Pendidikan pada Pengolahan Data Alumni - Hendriansyah; Efniar; Krisna, Robi; Nirmala, Violeta; Destikarini, Fartina (Journal of Social and Community Service, 2025)
The alumni tracking system is useful for tracking the whereabouts of alumni after graduating from vocational school. For schools, the alumni tracking system becomes an alumni database that can be accessed at any time and adds value during school accreditation. This system is useful as a liaison between the school and alumni so that ties between the school and alumni will continue to exist. The aim of this training is to produce alumni data that is accurate, fast, and can be used for decision making by the school after obtaining alumni search results. Searching for alumni data is made with display menus and features that are tailored to user needs and are dynamic so that at any time additions or improvements can be made easily. Processing alumni data at Bina Sriwijaya Vocational School uses Office but many shortcomings are still found. The Service Team concluded to create a website-based alumni data processing application at SMK Bina Sriwijaya Palembang. Information systems really support the progress of an institution. To build an effective website requires implementing certain strategies so that the website is able to achieve maximum results. This implementation method goes through the stages of planning, preparation, implementation. From the Pkm results, it was concluded that out of 50 participants, 41 people or 82% strongly agreed with the Website Creation Training and 9 people or 12% agreed and 0 people or 0% disagreed.